Technical Note: The Forensic Anthropology Society of Europe (FASE) Map of Identified Osteological Collections. (November 2021) - Petaros, Anja; Caplova, Zuzana; Verna, Emeline; Adalian, Pascal; Baccino, Eric; de Boer, Hans H.; Cunha, Eugenia; Ekizoglu, Oguzhan; Ferreira, Maria Teresa; Fracasso, Tony; Kranioti, Elena F.; Lefevre, Philippe; et al.
Highlights: FASE created a free online map on identified osteological collections worldwide. These collections are an important resource for anthropology research and training. The FASE map today counts 153 identified osteological collections in 41 countries. The number of identified contemporary osteological collections is continuously growing. Abstract: Identified (documented) osteological collections represent an important resource in the development of forensic anthropology standards and methods as well as a precious tool for learning and training of practitioners. Even though the number of papers presenting identified collections worldwide increases, many of the collections have still not been divulged to the scientific community in sufficient detail to ascertain their exact number. The Forensic Anthropology Society of Europe (FASE) therefore developed a tool that goes beyond sporadic publications: the FASE Map of Identified Osteological Collections, which is freely accessible and continuously updated and revised. The online map is available at http://forensicanthropology.eu/osteological-collections/ . The map of skeletal collections was created in 2017 and currently displays information on 153 identified osteological collections (43 of them categorized as contemporary) located in 41 different countries. This article offers a short analysis of the type, geographical location and content of the collections included in the map. The aim of this article and the map as such is to provide a useful resource to facilitate research planning and teaching in forensic anthropology and related disciplines.